Multisensory Perception And Action: Psychophysics, Neural Mechanisms, And Applications - Hermann Josef Mueller (Frontiers Research Topics, 2015)
Our senses are not separated. Information received from one sensory modality may be linked with, or distorted by information provided from another modality, such as in the ventriloquism illusion and experiences of crossmodal correspondence. Scientific interest in how we integrate multisensory information and how we interact with a multisensory world has increased dramatically over the last two decades, as evidenced by an exponential growth of relevant studies using behavioral and/or neuro-scientific approaches to investigate multisensory integration and the underlying brain mechanisms. This work has revealed that the brain integrates information across senses in a statistically optimal manner; also, some key multisensory brain areas, such as the superior colliculus, have been identified. However, many questions remain unresolved. For example, at what age do we develop optimal multisensory integration? How does the brain 'know' which stimuli to combine, and which to segregate? What are the principles that govern crossmodal interactions? Does multisensory integration rely solely on the variability of sensory information? Do primary sensory cortices also contribute to multisensory integration? How does multisensory integration influence our sensorimotor interactions? To take stock of the most recent developments, this Research Topic aims to provide a broad scope of research on multisensory perception and action from different perspectives/approaches and disciplines, including behavioral and neuro-sciences, computational/mathematical modeling, and engineering science. Specifically, the Research Topic will focus on the following topics: 1. Functional and behavioral mechanisms of multisensory perception 2. Neural mechanisms of multisensory coding 3. Multisensory perception and sensorimotor interaction 4. Multisensory applications